Fundamentalisme dan Radikalisme Islam - Ibnu Sahrul; Windi Afrilia; Agus Rifki Ridwan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Fundamentalism is one of the schools of thought that does not want to accept change in the sense that they oppose renewal. So, they carefully emphasize that the announcement of the prophethood of Muhammad SAW is not something new, but only continues the series of prophets and apostles who preceded him. Meanwhile, radicalism is a group that is often viewed by the West as a terrorist who aims to weaken political authority through jihad. This means that these radical religious movements make jihad one of the methods to achieve their ideals, namely the Islamic system (al-nizām al-Islāmi). In addition, radicals are considered narrow- minded, overly enthusiastic (ultra zeolous), or want to achieve their goals by using violent means. Therefore, it is understandable why most Muslim scholars view radicalism as an unfavorable term and cause misunderstanding. This view is also found in orientalists and Western scholars who understand Islam.